Electrolyte, lithium ion battery and electronic device
By using fluorinated solvents and polycarbonate solvents in lithium-ion batteries, the problems of degradation in performance and safety hazards of traditional batteries under high voltage conditions are solved, and high energy density and high cycle stability are achieved.
Patent Information
- Application Number
- CN202411821001.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-11
AI Technical Summary
Under high voltage conditions, the EC-based electrolyte's antioxidant capacity is limited, resulting in a decline in battery performance and an increase in safety risks, making it difficult to meet the growing demand for energy density and voltage windows.
An electrolyte including fluorinated solvent and polycarbonate solvent is adopted. The fluorinated solvent and polycarbonate solvent cooperate with each other to improve the storage performance and circulation performance of lithium-ion batteries under high temperature and high pressure.
The high voltage window and high energy density of lithium-ion batteries under high temperature and high pressure are realized, which significantly improves the cycle stability and safety performance of the battery.
Smart Images

Figure BDA0005183105210000021 
Figure BDA0005183105210000041 
Figure BDA0005183105210000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte and a lithium ion battery and an electronic device comprising the electrolyte. Background Art
[0002] As one of the most mainstream energy storage technologies, the performance improvement of lithium-ion batteries has become a hot topic of research. Although traditional lithium-ion battery systems, such as those based on graphite negative electrodes and EC (ethylene carbonate)-based electrolytes with NMC (nickel manganese cobalt ternary materials) / LCO (lithium cobalt oxide) positive electrodes, have been widely used in the market, their energy density and voltage window have gradually failed to meet the growing demand. Especially under high voltage conditions, the antioxidant capacity of EC-based electrolytes is limited, resulting in decreased battery performance and increased safety risks.
[0003] In order to overcome this bottleneck, it is imperative to develop a new electrolyte system with high voltage window, high energy density and excellent cycle stability. Summary of the invention
[0004] The present invention provides an electrolyte, a lithium ion battery and an electronic device comprising the electrolyte. The electrolyte of the present invention can improve the storage performance and cycle performance of the lithium ion battery under high temperature and high pressure. The lithium ion battery of the present invention has a high voltage window and high energy density.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] The first aspect of the present invention provides an electrolyte, the electrolyte comprising a fluorinated solvent and a polycarbonate solvent; the chemical formula of the polycarbonate solvent is shown in formula (I):
[0007]
[0008] wherein said R1 and said R2 are each independently selected from substituted or unsubstituted C1-C8 alkyl, substituted or unsubstituted C2-C5 alkenyl, substituted or unsubstituted C2-C4 alkynyl, substituted or unsubstituted C1-C8 alkoxy, wherein, when substituted, the substituents are each independently selected from halogen;
[0009] Based on the total mass of the electrolyte, the mass content of the fluorinated solvent is A wt%, the mass content of the polycarbonate solvent is B wt%, and the electrolyte satisfies the relationship: 0.5≤A / B≤20.
[0010] A second aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising an electrolyte and a negative electrode sheet, the electrolyte being the electrolyte described in the first aspect of the present invention;
[0011] The negative electrode sheet comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-carbon material, wherein the silicon-carbon material comprises a porous carbon substrate and nano-silicon particles located on the porous carbon substrate;
[0012] Preferably, the particle size Dv50 of the silicon-carbon material is 6 μm-12 μm;
[0013] Preferably, the thickness of the negative electrode sheet is 20 μm-300 μm.
[0014] Preferably, the mass content of element Si in the negative electrode active material is 1.5wt%-40wt%, preferably 3wt%-15wt%.
[0015] A third aspect of the present invention provides an electronic device, which includes the electrolyte described in the first aspect of the present invention or the lithium-ion battery described in the second aspect of the present invention.
[0016] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0017] By adding a fluorinated solvent and a polycarbonate solvent to the electrolyte of the present invention, the two solvents work together to improve the storage performance and cycle performance of the lithium ion battery under high temperature and high pressure; the lithium ion battery of the present invention has a high voltage window and high energy density.
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. DETAILED DESCRIPTION
[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0020] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0021] The first aspect of the present invention provides an electrolyte, the electrolyte comprising a fluorinated solvent and a polycarbonate solvent; the chemical formula of the polycarbonate solvent is shown in formula (I):
[0022]
[0023] Wherein, the R1 and the R2 are each independently selected from substituted or unsubstituted C1-C8 alkyl (e.g., -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, etc.), substituted or unsubstituted C2-C5 alkenyl (e.g., -CH=CH2, -CH=CH-CH3, -CH2-CH=CH2, etc.), substituted or unsubstituted C2-C4 alkynyl (e.g., -C≡CH, etc.), substituted or unsubstituted C1-C8 alkoxy (e.g., -OCH3, -OCH2CH3, -OCH2CH3CH3, -OCH(CH3)2), wherein, when substituted, the substituents are each independently selected from halogen (e.g., F, Cl, Br, I, etc.);
[0024] Based on the total mass of the electrolyte, the mass content of the fluorinated solvent is Awt%, the mass content of the polycarbonate solvent is Bwt%, and the electrolyte satisfies the relationship: 0.5≤A / B≤20, for example 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.
[0025] In the present invention, the electrolyte includes a fluorinated solvent and a polycarbonate solvent. The fluorine atoms in the fluorinated solvent have extremely strong electronegativity, which enables it to remain relatively stable under high voltage environment, not easily decomposed by oxidation or reduction, has thermodynamic oxidation resistance, and good high voltage stability. At the same time, the fluorinated solvent has good film-forming properties at the negative electrode, which can inhibit the occurrence of the reduction reaction of the electrolyte during the cycle, and has kinetic reduction resistance. Therefore, the fluorinated solvent can significantly improve the high-voltage cycle stability. However, the fluorinated solvent has poor high-temperature stability, and it is easy to increase the acidity, causing the battery to produce gas at high temperature. Polycarbonate not only has good high-voltage resistance, but also has good high-temperature stability. In addition, a polycarbonate solvent is further added to the electrolyte. The chemical formula of the polycarbonate solvent is shown in formula (I). When the two solvents are used together, the ester group in the polycarbonate can reduce the hydrogen ions generated at high temperature of the electrolyte, avoid the increase of electrolyte acidity, and also can relatively reduce the use of fluorinated solvents to avoid high-temperature gas production during the battery cycle. The two solvents work together to significantly improve the problem of poor storage performance of lithium-ion batteries under high temperature and high pressure, while also taking into account the cycle performance under high temperature and high pressure.
[0026] Further, based on the total mass of the electrolyte, the mass content of the fluorinated solvent is A wt%, the mass content of the polycarbonate solvent is B wt%, and the electrolyte satisfies the relationship: 0.5≤A / B≤20. When A / B<0.5, the mass content of the fluorinated solvent is too little, and the mass content of the polycarbonate solvent is too much. Although the polycarbonate solvent can reduce the hydrogen ions generated at high temperature of the electrolyte and avoid the increase of the acidity of the electrolyte, its excessive content will lead to an increase in the viscosity of the electrolyte and significantly deteriorate the kinetic properties of the electrolyte; when A / B>20, the mass content of the fluorinated solvent is too much, and the mass content of the polycarbonate solvent is too little, which will lead to poor temperature stability, easy to increase the acidity, and cause the battery to produce gas at high temperature. Therefore, the present invention can further improve the storage performance and cycle performance of lithium-ion batteries under high temperature and high pressure by controlling the content ratio of the two solvents within a suitable range, so that the lithium-ion battery of the present invention has a high voltage window.
[0027] In a preferred embodiment, the electrolyte satisfies the relationship: 1≤A / B≤8.
[0028] In the present invention, the mass content of the fluorinated solvent is A wt%, which satisfies 5wt%≤A wt%≤50wt%. For example, A wt% can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%. When the mass content A of the fluorinated solvent is higher than 50wt%, the gas production problem of the battery at high temperature may be aggravated due to the poor high temperature stability of the fluorinated solvent and the easy increase of acidity; when the mass content A of the fluorinated solvent is lower than 10wt%, the oxidation resistance of the electrolyte will be significantly reduced, and the stability of the negative electrode interface will be reduced; in addition, the fluorinated solvent generally has a high oxidation stability and can maintain the stability of the electrolyte at high voltage; if the amount added is insufficient, the electrolyte may be easily decomposed at high voltage, thereby reducing the cycle life of the battery; and if the amount of the fluorinated solvent added is too small, it may not be able to fully form a protective positive and negative electrode interface film, thereby affecting the cycle stability and overall performance of the lithium ion battery. Therefore, it is necessary to control the mass content of the fluorinated solvent in the electrolyte within an appropriate range. In a preferred embodiment, 10 wt % ≤ A wt % ≤ 40 wt %.
[0029] In the present invention, the mass content of the polycarbonate solvent is B wt%, which satisfies 2wt%≤B wt%≤30wt%. For example, B wt% can be 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%. Although the addition of a polycarbonate solvent can reduce the use of a fluorinated solvent, when the mass content of the polycarbonate solvent is higher than 30wt%, it will cause the viscosity of the electrolyte to increase and significantly deteriorate the kinetic properties of the electrolyte. Therefore, the mass content of the polycarbonate solvent should not be too much. In a preferred embodiment, 5wt%≤B wt%≤20wt%.
[0030] In the present invention, the electrolyte comprises ethylene carbonate and propylene carbonate. Based on the total mass of the electrolyte, the mass content of ethylene carbonate is C wt%, C wt%≤3wt%, for example, 3wt%, 2.9wt%, 2.8wt%, 2.7wt%, 2.6wt%, 2.5wt%, 2.4wt%, 2.3wt%, 2.2wt%, 2.1wt%, 2wt%, 1.9wt%, 1.8wt%, 1.7wt%, 1.6wt%, 1.5wt%, 1.4wt%, 1.3wt%, 1.2wt%, 1.1wt%, 1wt%, 0.9wt%, 0.8wt%, 0.7wt%, 0.6wt%, 0.5wt%, 0.4wt%, 0.3wt%, 0.2wt%, 0.1wt% or 0wt%; ethylene carbonate (EC) is a cyclic carbonate with poor oxidation resistance, and its content should not be too high, so as to improve the overall oxidation resistance of the electrolyte and further improve the high temperature and high pressure stability of the battery; the mass content of propylene carbonate is D wt%, D wt% ≥ 5wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%; and propylene carbonate (PC) has good oxidation resistance and a high dielectric constant, and can improve the conductivity and kinetics of the electrolyte. Properly controlling its content within a suitable range can improve the cycle stability of the battery at a larger rate, thereby further enhancing the high temperature and high pressure cycle performance of the lithium-ion battery.
[0031] Moreover, the present invention controls the electrolyte to satisfy the relationship 0.05≤C / D≤0.6 (for example, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6), or C / D=0, that is, the ratio of the mass content of ethylene carbonate to propylene carbonate satisfies the above relationship, and can have higher dynamic performance, thereby further stabilizing the cycle performance of the lithium ion battery under high temperature and high pressure. This is because although PC has a high dielectric constant, it can improve The conductivity and kinetics of the electrolyte improve the cycle stability at a larger rate, but it is easy to decompose during the battery cycle, especially under high voltage conditions, which will lead to a decrease in the kinetic performance of the electrolyte. Therefore, the mass content D of PC should not be too high, C / D is greater than or equal to 0.05; at the same time, EC has poor oxidation resistance, and its content should not be too high. It is necessary to control its content so that it is not too high, thereby improving the overall oxidation resistance of the electrolyte, C / D is less than or equal to 0.6; moreover, EC can also be omitted, at which time C / D = 0. In summary, the mass content of EC and PC can satisfy the relationship 0≤C / D≤0.6, and the storage performance and cycle performance of lithium-ion batteries under high temperature and high pressure can be significantly improved while ensuring that the electrolyte has high kinetic performance.
[0032] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the propylene carbonate is D wt %, 7wt%≤D wt%≤20wt%.
[0033] In the present invention, the fluorinated solvent includes at least one of trifluoroethyl methyl carbonate (FEMC), 2,2-difluoroethyl acetate (DFEA), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (HFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), fluorodiethyl carbonate (FDEC), ethyl 2,2,2-trifluoroacetate (FEA), and 1,4-difluorobenzene.
[0034] In the present invention, the polycarbonate solvent comprises at least one of the compounds of formula (I-1) to formula (I-6) shown below:
[0035]
[0036] In the present invention, the electrolyte further includes a lithium salt, and the lithium salt includes lithium bis(trifluoromethylsulfonyl)imide and lithium hexafluorophosphate. Based on the total mass of the electrolyte, the mass content of the lithium salt is 15wt%-30wt%. Exemplarily, the mass content of the lithium salt can be 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, or 30wt%.
[0037] Wherein, the mass content of the lithium bis(trifluoromethylsulfonyl)imide is ≥3wt%, for example, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%.
[0038] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the lithium salt is 17wt%-23wt%.
[0039] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the lithium bis(trifluoromethylsulfonyl)imide is 4wt%-8wt%.
[0040] A higher content of lithium salt can increase the concentration of lithium ions in the negative electrode electrolyte. The lithium ion concentration of the negative electrode electrolyte will drop significantly during fast charging. A higher initial lithium ion concentration can prevent the depletion of the lithium ion concentration of the negative electrode electrolyte during fast charging. If the lithium ion concentration is too low, the negative electrode is prone to lithium precipitation, so a higher lithium salt content can significantly improve the electrolyte dynamics, reduce the risk of lithium precipitation under high-rate cycling, and improve the cycle stability of lithium-ion batteries. Furthermore, by controlling the mass content of lithium bis(trifluoromethylsulfonyl)imide to be greater than 3wt%, the stability and oxidation resistance of high lithium salts can be improved, and the HF generated by high lithium salts can be reduced.
[0041] Moreover, a higher content of lithium bis(trifluoromethylsulfonyl)imide can improve the kinetic properties of the electrolyte, compensating for the deterioration of the kinetic properties of the electrolyte after the addition of a polycarbonate solvent, so that the simultaneous addition of a high content of lithium bis(trifluoromethylsulfonyl)imide and a polycarbonate solvent can allow the electrolyte to have both excellent kinetic properties and high-voltage stability, thereby further stabilizing the storage performance and cycle performance of lithium-ion batteries under high temperature and high pressure.
[0042] In the present invention, the electrolyte further comprises an additive, and the additive comprises at least one of fluoroethylene carbonate (FEC), fluorophosphate and ethoxy pentafluorocyclophosphazene.
[0043] In the present invention, at least one of fluoroethylene carbonate, fluorophosphate and ethoxy pentafluorocyclophosphazene is added as an additive to the electrolyte. Since fluoroethylene carbonate, fluorophosphate and ethoxy pentafluorocyclophosphazene all have a certain flame retardant effect, the furnace temperature safety performance of the lithium ion battery can be improved, and the safety performance and service life of the battery can be significantly improved. In addition, fluoroethylene carbonate, fluorophosphate and ethoxy pentafluorocyclophosphazene can form a stable solid electrolyte film on the surface of the electrode. The film can effectively block the direct contact between the electrolyte and the electrode material, reduce adverse reactions, and help improve the interface compatibility between the electrode and the electrolyte, thereby further improving the cycle stability of the battery under high temperature and high pressure.
[0044] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the fluoroethylene carbonate is 0.1wt%-20wt%. Exemplarily, the mass content of the fluoroethylene carbonate can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 10wt%, 15wt%, 20wt%; the mass content of the fluorophosphate is 0.1wt%-5wt%. Exemplarily, the mass content of the fluorophosphate can be 0.1wt%, 0.2wt%, 0. .3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%; the mass content of the ethoxy pentafluoro cyclophosphazene is 0.1wt%-5wt%, exemplary, the mass content of the ethoxy pentafluoro cyclophosphazene can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%.
[0045] In a specific embodiment, the fluorophosphate ester includes at least one of tris(2,2,2-trifluoroethyl)phosphate and tris(2,2,2-trifluoroethyl)phosphate.
[0046] In the present invention, the additives further include sulfur-containing additives and / or nitrile additives.
[0047] In a specific embodiment, the sulfur-containing additive includes at least one of 1,3-propane sultone (PS), 1-propylene-1,3-sultone, 5-methyloxathiolane 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone and 1,4-butane sultone.
[0048] In a specific embodiment, the nitrile additive includes one or more of 1,3,5-hexanetrinitrile, adiponitrile, succinonitrile, ethylene glycol bis(propionitrile) ether and tris(3-cyanopropyl) phosphate.
[0049] A second aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising an electrolyte and a negative electrode sheet, the electrolyte being the electrolyte described in the first aspect of the present invention;
[0050] The negative electrode sheet comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-carbon material, and the silicon-carbon material comprises a porous carbon substrate and nano-silicon particles located on the porous carbon substrate.
[0051] Since the size of nano silicon particles is very small and they are evenly dispersed in the porous carbon substrate material, the SEI damage caused by silicon expansion can be significantly reduced, and the battery cycle performance can be significantly improved compared with other silicon materials. Moreover, fluorinated solvents can be reduced on the surface of silicon-containing negative electrode sheets to form a protective film rich in LiF. This protective film is not only chemically stable, but also mechanically stable, so it can significantly improve the compatibility of electrolyte and silicon-doped negative electrode sheets; further, nano silicon is used. Since the size of nano silicon particles is much smaller than that of micron silicon particles, they have a larger specific surface area, thereby increasing the diffusion rate and adsorption capacity of lithium ions, which helps to improve the fast charging cycle performance of the battery; and due to their small size, the strain energy of nano silicon particles will be relatively reduced. Therefore, relatively speaking, nano silicon particles are less likely to cause negative electrode structure rupture and capacity attenuation due to volume changes, which is more conducive to improving the overall performance of the battery under high temperature and high pressure.
[0052] In a specific embodiment, the particle size Dv50 of the silicon-carbon material is 5μm-15μm. For example, the particle size Dv50 of the silicon-carbon material can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm; the particle size Dv50 of the silicon-carbon material can be measured using a laser particle size analyzer, the silicon-carbon material is evenly dispersed in the solution, and the laser particle size analyzer is used to analyze and calculate the particle size Dv50 of the silicon-carbon material. Dv50 refers to the particle size corresponding to the cumulative particle size distribution percentage reaching 50% in the volume distribution. If the particle size Dv50 of the silicon-carbon material is too large, it will cause uneven stress distribution inside the electrode, increase the risk of electrode rupture, and thus reduce the cycle stability of the battery. If the particle size Dv50 of the silicon-carbon material is too small, it will cause excessive growth of SEI and generate a thicker solid electrolyte interface (SEI) film, which will not only increase the internal resistance of the battery, but also cause rapid loss of battery capacity.
[0053] In the present invention, the negative electrode active material may also include a carbon-based negative electrode material, and the carbon-based negative electrode material may include artificial graphite, graphite, hard carbon and other carbon-based negative electrode materials commonly used in the art.
[0054] In the present invention, the mass content of element Si in the negative electrode active material is 1.5wt%-40wt%. For example, the mass content of element Si can be 1.5wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%. In a preferred embodiment, the mass content of element Si is 3wt%-15wt%. The mass content of element Si in the negative electrode active material can be detected by ICP plasma reflectometer and other methods. By controlling the mass content of element Si in the negative electrode active material, the present invention can further adjust the relative content and dispersion uniformity of nano-silicon particles in the porous carbon substrate material, which can alleviate the negative electrode structure rupture and capacity attenuation caused by volume change of silicon-carbon material, and is more suitable for lithium-ion batteries under high temperature and high pressure systems, and improves its cycle stability under high temperature and high pressure.
[0055] In the present invention, the thickness of the negative electrode sheet is 20 μm-300 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm. The thickness of the negative electrode sheet refers to the total thickness of the negative electrode current collector and the negative electrode active coating disposed on both sides of the negative electrode current collector. By controlling the thickness of the negative electrode sheet, the coating amount of the negative electrode active material on the surface of the negative electrode current collector can be adjusted, which can provide a buffer space for the volume expansion of the silicon-carbon material and reduce the damage to the electrode structure caused by expansion, thereby further improving the cycle stability of the lithium-ion battery.
[0056] According to the lithium ion battery of the present invention, the lithium ion battery further comprises a separator, and the separator may also be a separator conventionally used in the art, such as a PP film, a PE film, and the like.
[0057] According to the lithium ion battery of the present invention, the lithium ion battery further comprises a positive electrode sheet, and the positive electrode sheet can be a positive electrode sheet conventionally used in the art.
[0058] The lithium-ion battery of the invention can be prepared by conventional methods in the art. Specifically, the positive electrode, the isolation membrane and the negative electrode can be stacked in sequence, and then the battery cell can be obtained through the processes of baking, liquid injection, formation, packaging, etc.
[0059] A third aspect of the present invention provides an electronic device, which includes the electrolyte described in the first aspect of the present invention or the lithium-ion battery described in the second aspect of the present invention.
[0060] The present invention does not limit the types of electronic devices, and specifically may include but is not limited to laptop computers, input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0061] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0062] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0063] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] Example 1
[0065] The lithium ion battery of the present invention is obtained by the following method:
[0066] 1) Preparation of positive electrode
[0067] The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.
[0068] 2) Negative electrode preparation
[0069] The negative electrode active material artificial graphite, silicon carbon material (particle size Dv50 is 8 μm), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 84.5:10:2.5:1.5:1:0.5, deionized water is added, and the negative electrode active slurry is obtained under the action of a vacuum mixer. The mass content of element Si in the negative electrode active slurry is measured to be 5wt%; the negative electrode active slurry is evenly coated on both surfaces of the copper foil; the coated copper foil is dried at room temperature, and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet with a thickness of 100 μm.
[0070] 3) Preparation of electrolyte
[0071] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), the solvent fluorinated solvent (1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether) / polycarbonate (Formula (I-1)) / EC / PC / PP was uniformly mixed in a mass ratio of A:B:C:D:(100-ABC), and then 12.5wt% of fully dried lithium hexafluorophosphate (LiPF6) and 4wt% of lithium bis(trifluoromethylsulfonyl)imide based on the total mass of the electrolyte were quickly added thereto. (LiTFSI), the specific substances and addition amounts are as described in Table 1, and then 3wt% 1,3-propane sultone (PS), 1wt% fluoroethylene carbonate (FEC), 1wt% tris (2,2,2-trifluoroethyl) phosphate and 1wt% ethoxypentafluorocyclophosphazene, as well as nitrile additives 2wt% 1,3,5 hexane trinitrile (HTCN) and 1wt% adiponitrile (ADN) are added based on the total mass of the electrolyte. After stirring evenly, the desired electrolyte is obtained after the moisture and free acid tests are qualified.
[0072] 4) Preparation of lithium-ion batteries
[0073] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and after vacuum packaging, standing, forming, shaping, sorting and other processes, the separator redundancy is controlled to B, and the specific amount is as described in Table 1 to obtain a lithium ion battery. The battery of the present invention has a charge and discharge range of 3.0-4.58V.
[0074] Example 2 Group
[0075] This example is carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed, so that the mass content Awt% of the fluorinated solvent is changed, as shown in Table 1 for details.
[0076] Example 3 Group
[0077] This example is carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed, so that the mass content Bwt% of the polycarbonate is changed, as shown in Table 1 for details.
[0078] Example 4 Group
[0079] This example is carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed, so that the content C wt % of the solvent ethylene carbonate is changed, as shown in Table 1 for details.
[0080] Example 5 Group
[0081] This example is carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed, so that the content D wt % of the solvent propylene carbonate is changed, as shown in Table 1 for details.
[0082] Example 6 Group
[0083] This example is carried out with reference to Example 1, with the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed so that the mass content C wt % of the solvent ethylene carbonate and the content D wt % of propylene carbonate are changed simultaneously, as shown in Table 1 for details.
[0084] Example 7 Group
[0085] This example is carried out with reference to Example 1, with the only difference being that, during the preparation of the electrolyte, the mass content of lithium salt lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) is changed, as shown in Table 1 for details.
[0086] Example 8 Group
[0087] This example is carried out with reference to Example 1, except that, during the preparation of the electrolyte, the mass contents of the additives fluoroethylene carbonate, tris(2,2,2-trifluoroethyl)phosphate and ethoxypentafluorocyclophosphazene are changed, as shown in Table 1 for details.
[0088] Example 9 Group
[0089] This embodiment is carried out with reference to the embodiment 1, the only difference being that the particle size Dv50 range of the silicon-carbon material is adjusted, specifically:
[0090] In Example 9-1, the particle size Dv50 of the silicon carbon material used is 6 μm;
[0091] In Example 9-2, the particle size Dv50 of the silicon carbon material used is 15 μm.
[0092] Example 10 Group
[0093] This embodiment is carried out with reference to the embodiment 1, the only difference being that the relative content of nano-silicon on the surface of the porous carbon substrate material in the silicon-carbon negative electrode material is adjusted so that the mass content of element Si in the negative electrode active slurry is changed, specifically:
[0094] In Example 10-1, the mass content of element Si in the negative electrode active slurry is 15 wt %;
[0095] In Example 10-1, the mass content of element Si in the negative electrode active slurry is 35 wt %.
[0096] Comparative Example 1
[0097] This comparative example was carried out with reference to Example 1, the only difference being that no fluorinated solvent was added during the preparation of the electrolyte, as shown in Table 1 for details.
[0098] Comparative Example 2
[0099] This comparative example was carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, no polycarbonate solvent was added, as shown in Table 1 for details.
[0100] Comparative Example 3
[0101] This comparative example is carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed, so that the mass content Awt% of the fluorinated solvent and the mass content Bwt% of the polycarbonate are changed, as shown in Table 1 for details.
[0102] Comparative Example 4
[0103] This comparative example is carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed, so that the mass content Awt% of the fluorinated solvent and the mass content Bwt% of the polycarbonate are changed, as shown in Table 1 for details.
[0104] Comparative Example 4
[0105] This comparative example is carried out with reference to Example 1, the only difference being that, during the preparation of the electrolyte, the mass ratio of each solvent component is changed, so that the mass content Awt% of the fluorinated solvent and the mass content Bwt% of the polycarbonate are changed, as shown in Table 1 for details.
[0106] Table 1
[0107]
[0108]
[0109] The lithium-ion batteries obtained in the above examples and comparative examples were subjected to high temperature cycle and high temperature storage performance tests, respectively. The test results are shown in Table 2.
[0110] 1) Cyclic performance test at room temperature 25℃
[0111] The battery in Table 1 was charged and discharged in a 2C discharge range at 25°C within the charge and discharge cut-off voltage range. The discharge capacity of the first week of the test was calculated as x1mAh, and the discharge capacity of the Nth cycle was calculated as y1mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R1=y1 / x1 of the Nth week. The number of battery cycles / T when the cycle capacity retention rate R1 was 80% was recorded. The results are shown in Table 2.
[0112] 2) High temperature 45℃ cycle performance test
[0113] The battery in Table 1 was charged and discharged in a cycle at 45°C at a discharge rate of 2C within the charge and discharge cut-off voltage range. The discharge capacity of the first week of the test was calculated as x2mAh, and the discharge capacity of the Nth cycle was calculated as y2mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R2=y2 / x2 of the Nth week. The number of cycles of the battery when the cycle capacity retention rate R2 is 80% was recorded. The results are shown in Table 2.
[0114] 3) High temperature 60℃ storage performance test
[0115] The battery in Table 1 was charged at 1C rate to the cut-off voltage at 25°C, the cut-off current was 0.025C, and it was left to stand for 5 minutes. The thickness of the lithium-ion battery was tested (this was the thickness before storage). The fully charged cell / battery was placed in an open circuit at (60±2)°C for 35 days. After 35 days of storage, it was placed in an open circuit at room temperature for 2 hours. The cold thickness after storage was measured, and the thickness expansion rate of the lithium-ion battery was calculated: thickness expansion rate = [(thickness after storage - thickness before storage) / thickness before storage] × 100%. The results are shown in Table 2.
[0116] Table 2
[0117]
[0118]
[0119] By adding a fluorinated solvent and a polycarbonate solvent to the electrolyte of the present invention, the two solvents work together to solve the problem of poor storage performance of lithium-ion batteries under high temperature and high pressure. Compared with comparative examples 1-5, Example 1 has excellent high-temperature cycle capacity retention rate and high-temperature storage performance; moreover, by adding ethylene carbonate and propylene carbonate solvents and controlling the relationship between the total amount of ethylene carbonate and propylene carbonate solvents and the content of the polycarbonate solvent, the kinetic properties of the electrolyte can be further improved, thereby stabilizing the cycle capacity retention rate and thickness expansion rate of lithium-ion batteries under high temperature and high pressure.
[0120] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes a fluorinated solvent and a polycarbonate solvent; the chemical formula of the polycarbonate solvent is shown in formula (I): wherein said R1 and said R2 are each independently selected from substituted or unsubstituted C1-C8 alkyl, substituted or unsubstituted C2-C5 alkenyl, substituted or unsubstituted C2-C4 alkynyl, substituted or unsubstituted C1-C8 alkoxy, wherein, when substituted, the substituents are each independently selected from halogen; Based on the total mass of the electrolyte, the mass content of the fluorinated solvent is A wt%, the mass content of the polycarbonate solvent is B wt%, and the electrolyte satisfies the relationship: 0.5≤A / B≤20.
2. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass content of the fluorinated solvent is A wt%, satisfying 5wt%≤A wt%≤50wt%, preferably, 10wt%≤A wt%≤40wt%; and / or, based on the total mass of the electrolyte, the mass content of the polycarbonate solvent is B wt%, satisfying 2wt%≤B wt%≤30wt%, preferably, 5wt%≤B wt%≤20wt%; And / or, the electrolyte satisfies the relationship: 1≤A / B≤8.
3. The electrolyte according to claim 1, characterized in that The electrolyte includes ethylene carbonate and propylene carbonate; Based on the total mass of the electrolyte, the mass content of the ethylene carbonate is C wt%, C wt%≤3wt%, and the mass content of the propylene carbonate is D wt%, Dwt%≥5wt%; the electrolyte satisfies the relationship: 0.05≤C / D≤0.6, or C / D=0; Preferably, 7 wt%≤D wt%≤20 wt%.
4. The electrolyte according to claim 1, characterized in that The fluorinated solvent includes at least one of methyl trifluoroethyl carbonate, 2,2-difluoroethyl acetate, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, diethyl fluorocarbonate, ethyl 2,2,2-trifluoroacetate, and 1,4-difluorobenzene.
5. The electrolyte according to claim 1, characterized in that The polycarbonate solvent comprises at least one of the compounds of formula (I-1) to formula (I-6) shown below:
6. The electrolyte according to claim 1, characterized in that The electrolyte further comprises a lithium salt, wherein the lithium salt comprises lithium bis(trifluoromethylsulfonyl)imide and lithium hexafluorophosphate, and the mass content of the lithium salt is 15wt%-30wt% based on the total mass of the electrolyte; Wherein, the mass content of the lithium bis(trifluoromethylsulfonyl)imide is ≥3wt%.
7. The electrolyte according to claim 1, characterized in that The electrolyte further comprises an additive, wherein the additive comprises at least one of fluoroethylene carbonate, fluorophosphate and ethoxy pentafluorocyclophosphazene; Preferably, based on the total mass of the electrolyte, the mass content of the fluoroethylene carbonate is 0.1wt%-20wt%; Preferably, based on the total mass of the electrolyte, the mass content of the fluorophosphate is 0.1wt%-5wt%; Preferably, based on the total mass of the electrolyte, the mass content of the ethoxy pentafluorocyclophosphazene is 0.1 wt%-5 wt%.
8. The electrolyte according to claim 7, characterized in that The additives also include sulfur-containing additives and / or nitrile additives; Preferably, the sulfur-containing additive includes at least one of 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methyloxathiolane 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone and 1,4-butane sultone; Preferably, the nitrile additive includes one or more of 1,3,5-hexanetrinitrile, adiponitrile, succinonitrile, ethylene glycol bis(propionitrile) ether and tris(3-cyanopropyl)phosphate.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises an electrolyte and a negative electrode sheet, wherein the electrolyte is the electrolyte according to any one of claims 1 to 8; The negative electrode sheet comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-carbon material, wherein the silicon-carbon material comprises a porous carbon substrate and nano-silicon particles located on the porous carbon substrate; Preferably, the particle size Dv50 of the silicon-carbon material is 5 μm-15 μm; Preferably, the thickness of the negative electrode sheet is 20 μm-300 μm; Preferably, the mass content of element Si in the negative electrode active material is 1.5wt%-40wt%, preferably 3wt%-15wt%.
10. An electronic device, characterized in that: The electronic device comprises the electrolyte according to any one of claims 1 to 8 or the lithium ion battery according to claim 9.
Citation Information
Patent Citations
Ether-group-containing dicarbonate compound for non-aqueous electrolyte, non-aqueous electrolyte containing ether-group-containing dicarbonate compound, and secondary battery
CN113206298A
Lithium ion battery
CN115064762A
Electrolyte, lithium ion battery and electric device
CN118645699A
Lithium ion battery electrolyte and lithium ion battery
CN118825406A
Nonaqueous electrolytic solution, and nonaqueous electrolytic battery arranged by use thereof
JP2014194930A
Cited By
Electrolyte and lithium ion battery
CN120109296A